2008
DOI: 10.1211/jpp.60.5.0009
|View full text |Cite
|
Sign up to set email alerts
|

ABCC2 haplotype is not associated with drug-resistant epilepsy

Abstract: Several studies have investigated the association between the ABCB1 polymorphism and drug-resistant epilepsy. However, the effect of ABCC2 polymorphisms on anti-epileptic drug (AED) responsiveness remains unknown. The ABCC2 polymorphisms have been genotyped in 279 Japanese epileptic patients treated with AEDs. The association between the AED responsiveness and the polymorphisms was estimated by a haplotype-based analysis. No genotype or haplotype was associated with drug-resistant epilepsy. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…Several previous studies have reported an association between the ABCC2 rs2273697 and rs717620 polymorphisms and risk of drug-resistant epilepsy, but with conflicting results (Seo et al, 2008;Kwan et al, 2011;Hilger et al, 2012;Qu et al, 2012;Sporis et al, 2013;Subenthiran et al, 2013a;Escalante-Santiago et al, 2014;Ma et al, 2014). Qu et al (2012) revealed a significant association between the ABCC2 rs2273697 and rs717620 polymorphisms and resistance to antiepileptic drugs in Chinese epileptic patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several previous studies have reported an association between the ABCC2 rs2273697 and rs717620 polymorphisms and risk of drug-resistant epilepsy, but with conflicting results (Seo et al, 2008;Kwan et al, 2011;Hilger et al, 2012;Qu et al, 2012;Sporis et al, 2013;Subenthiran et al, 2013a;Escalante-Santiago et al, 2014;Ma et al, 2014). Qu et al (2012) revealed a significant association between the ABCC2 rs2273697 and rs717620 polymorphisms and resistance to antiepileptic drugs in Chinese epileptic patients.…”
Section: Discussionmentioning
confidence: 96%
“…Ma et al (2014) reported a possible correlation between the ABCC2 rs2273697 polymorphism and resistance to antiepileptic drugs in 453 Chinese Han patients with epilepsy. However, other studies have reported that the ABCC2 rs2273697 and rs717620 polymorphisms were not associated with resistance to antiepileptic drugs (Seo et al, 2008;Kwan et al, 2011;Hilger et al, 2012;Sporis et al, 2013). In this study, we reported a significant correlation between the ABCC2 rs717620 polymorphism and resistance to antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 96%
“…Among the AEDs studied, only TPM showed a twofold increase [121]. A recent study failed to find a significant association between MRP2 haplotype and drug resistance in 279 Japanese epilepsy patients, although the delGCGC haplotype of G-a774delG, C-24T, G1249A, and C3972T was over-represented among patients with mental retardation in comparison with patients who did not have this condition [122]. Despite the great efforts devoted to research, the association of MRPs and MDR1 genetic variations with clinical phenotype has not yet been elucidated.…”
Section: -4 Transportersmentioning
confidence: 90%
“…Among the remaining 38 articles, 14 publications were reviews, 3 were meeting abstracts, 12 were not case-control studies, 2 did not present the usable data, and 1 was not in HWE; these studies were also excluded. Finally, a total of 6 published studies, comprising 1113 controls with drug-responsive epilepsy and 1100 patients with drug-resistant epilepsy, concerning G1249A polymorphism in the ABCC2 gene and the risk of resistance to AEDs were included in our meta-analysis (Seo et al, 2008;Kim et al, 2009;Ufer et al, 2009Ufer et al, , 2011Kwan et al, 2011;Qu et al, 2012). The characteristics of the included studies are listed in Table 1.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Ufer et al (2011) discovered a significant association between the ABCC2 G1249A polymorphism and drug-resistant epilepsy. However, other studies were unable to replicate this finding (Seo et al, 2008;Kim et al, 2009;Ufer et al, 2009;Kwan et al, 2011;Hilger et al, 2012). In view of the uncertainty surrounding this issue and considering the potential importance of this polymorphism for the response to anticonvulsant medication, we carried out this meta-analysis of all the relevant published literature using different genetic model analyses.…”
mentioning
confidence: 99%